Paclitaxel-terminated peptide brush polymers. Issue 50 (22nd May 2020) - Zhu, Jialei; Sun, Hao; Callmann, Cassandra E.; Thompson, Matthew P.; Battistella, Claudia; Proetto, Maria T.; Carlini, Andrea S.; Gianneschi, Nathan C.
Abstract : In this paper, we report the preparation of paclitaxel-terminated peptide brush polymers wherein cell uptake and toxicity are tunable based on peptide sequence. Abstract : In this paper, we report the preparation of paclitaxel-terminated peptide brush polymers wherein cell uptake and toxicity are tunable based on peptide sequence. Synthesis was enabled using a new paclitaxel-containing chain termination agent for ring-opening metathesis polymerization (ROMP). Critically, reverse phase HPLC could be used to efficiently separate peptide brush polymers consisting of one fluorophore and one terminal paclitaxel from crude polymer mixtures. These purified terminally-modified polymers showed greater potency than the original mixtures. Drug-terminated peptide brush polymers carrying positive charges exhibited enhanced cell uptake and cytotoxicity as compared to their neutral and negatively charged analogues.